The Evidence of Populism in the Narratives of the President of Brazil during the Covid-19 Pandemic - Souza, Cibele Silva e (KOME, 2024)
In Brazil, the period of the Covid-19 pandemic was characterised by a crisis reflected in social platforms and the centralisation of information in the hands of the political leader. This article analyses former President Bolsonaro’s political communication on Twitter (currently known as X) in a populist context. To achieve this objective, the research sets out from the idea that populist leaders have focused attention on publicising their popularity and approaching the public, a process expanded through social media. As a result of content analysis and studies by Engesser et al. (2017), five recurring narrative motifs were observed in Bolsonaro’s communication: attacks on traditional media, advocate of the people, the basis of religion and faith as a doctrine, the sovereignty of the nation, and appeals to the heart and opposition to the dominant structure. Based on the findings, the article contributes to studies on populism, placing the phenomenon in a media environment composed of political, social and economic uncertainty.